If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5p + 3)(5p + 3) = 8 Reorder the terms: (3 + 5p)(5p + 3) = 8 Reorder the terms: (3 + 5p)(3 + 5p) = 8 Multiply (3 + 5p) * (3 + 5p) (3(3 + 5p) + 5p * (3 + 5p)) = 8 ((3 * 3 + 5p * 3) + 5p * (3 + 5p)) = 8 ((9 + 15p) + 5p * (3 + 5p)) = 8 (9 + 15p + (3 * 5p + 5p * 5p)) = 8 (9 + 15p + (15p + 25p2)) = 8 Combine like terms: 15p + 15p = 30p (9 + 30p + 25p2) = 8 Solving 9 + 30p + 25p2 = 8 Solving for variable 'p'. Reorder the terms: 9 + -8 + 30p + 25p2 = 8 + -8 Combine like terms: 9 + -8 = 1 1 + 30p + 25p2 = 8 + -8 Combine like terms: 8 + -8 = 0 1 + 30p + 25p2 = 0 Begin completing the square. Divide all terms by 25 the coefficient of the squared term: Divide each side by '25'. 0.04 + 1.2p + p2 = 0 Move the constant term to the right: Add '-0.04' to each side of the equation. 0.04 + 1.2p + -0.04 + p2 = 0 + -0.04 Reorder the terms: 0.04 + -0.04 + 1.2p + p2 = 0 + -0.04 Combine like terms: 0.04 + -0.04 = 0.00 0.00 + 1.2p + p2 = 0 + -0.04 1.2p + p2 = 0 + -0.04 Combine like terms: 0 + -0.04 = -0.04 1.2p + p2 = -0.04 The p term is 1.2p. Take half its coefficient (0.6). Square it (0.36) and add it to both sides. Add '0.36' to each side of the equation. 1.2p + 0.36 + p2 = -0.04 + 0.36 Reorder the terms: 0.36 + 1.2p + p2 = -0.04 + 0.36 Combine like terms: -0.04 + 0.36 = 0.32 0.36 + 1.2p + p2 = 0.32 Factor a perfect square on the left side: (p + 0.6)(p + 0.6) = 0.32 Calculate the square root of the right side: 0.565685425 Break this problem into two subproblems by setting (p + 0.6) equal to 0.565685425 and -0.565685425.Subproblem 1
p + 0.6 = 0.565685425 Simplifying p + 0.6 = 0.565685425 Reorder the terms: 0.6 + p = 0.565685425 Solving 0.6 + p = 0.565685425 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + p = 0.565685425 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + p = 0.565685425 + -0.6 p = 0.565685425 + -0.6 Combine like terms: 0.565685425 + -0.6 = -0.034314575 p = -0.034314575 Simplifying p = -0.034314575Subproblem 2
p + 0.6 = -0.565685425 Simplifying p + 0.6 = -0.565685425 Reorder the terms: 0.6 + p = -0.565685425 Solving 0.6 + p = -0.565685425 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + p = -0.565685425 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + p = -0.565685425 + -0.6 p = -0.565685425 + -0.6 Combine like terms: -0.565685425 + -0.6 = -1.165685425 p = -1.165685425 Simplifying p = -1.165685425Solution
The solution to the problem is based on the solutions from the subproblems. p = {-0.034314575, -1.165685425}
| 16x=-73 | | -64x=-1280 | | -7x-3(5x+12)=-146 | | -64x=1280 | | 7+x-(3+32/8)=3 | | X/18=X/960 | | 5(y-3)=8(y-6) | | 2/3=4/5m | | 5t-5=7+2a | | 36=1y+5y+12 | | 14u+4u-15u-2u=8 | | 6(6x+6)-5=1+6v | | -21/(x^2+3) | | 8w-2(2+w)=25 | | -7x-6(-2x+10)=-115 | | 5(2+5x)=-28+6x | | 114=10.5x+30 | | y/-15-112=-88 | | -9g+13g=-12 | | 4log^10(3x)=8 | | 2x+12x-2=0 | | -10=b/7 | | 3v+12=-15forv | | 13x+15=1x-25 | | 7/3x+1/3x=3x+12/3+5/3x | | -3x-2x+1=16 | | 1/4x=20 | | -7x-6(2x+10)=-115 | | 4r+r+2r-5-4r+10=r | | -5y-(15y-1)=2(7y-16)-y | | 8x^2+2x+12=3x^2+11x+19 | | 7n-5n-n=8 |